Design of an integrated gate irrigation system with measurement and control based on Cloud-Edge-End collaboration and fuzzy algorithm - Wang, Xingchen; Zhang, Ying; Jin, Liyong; Ni, Jun; Zhu, Yan; Cao, Weixing; Jiang, Xiaoping (Computers and electronics in agriculture, 2025)
•The “Cloud-Edge-End” architecture enables real-time, precise irrigation management.•The Integrated system features precision control, stable performance, and a user-friendly HMI.•Fuzzy logic control ensures accurate gate regulation and stable flow control. In response to challenges such as outdated agricultural irrigation canal infrastructure and inefficient control and management methods, which result in low water resource utilization, a measurement and control integrated gate irrigation system based on the STM32 embedded microprocessor (STM32) has been developed. The system is based on the “Cloud-Edge-End” collaborative architecture (CEEA), utilizing agricultural Internet of Things (IoT) technologies such as advanced sensors, embedded systems, and wireless communication, and employs fuzzy logic (FL) control. The gate body is designed as a reliable, stable, and adjustable sliding plate structure. The opening and closing mechanism utilize a stepper motor to directly drive the threaded vice, generating a lifting movement of the gate plate. The control system includes key modules such as the main control unit, photovoltaic power supply, data acquisition, wireless communication, motor drive, and other essential components. The cloud platform facilitates remote monitoring and human–machine interaction via both web and mobile terminals, enabling convenient operation and data visualization. The regulation and control of the gate system is based on in-situ edge calculation by the master controller, which integrates the target flow rate with the real-time monitored flow rate. The FL control ensures accurate and stable regulation of the gate opening and flow rate. The performance test and experimental verification (during the rice jointing period) show that the integrated measurement and control gate system offers high regulation and control accuracy. Among them, the relative errors of local control and remote control are about 1 %, and the effect of local control is better than that of remote control. The correlations between the flow rate and the gate opening, as well as between the flow rate and the water level behind the gate are both relatively high. R2 of the latter is as high as 0.99. Additionally, the relative error of the automatic flow control remains within ± 5 %, indicating that the system exhibits high precision in flow regulation and control. The system is particularly suitable for small and medium sized agricultural irrigation and drainage projects, providing new equipment support for the advancement of modern agricultural water conservation technology.